The stability of deposits in the Interest-Based and Interest-Free Banking Systems in Malaysia - Remali Yusoff; Wilson, Rodney (Penerbit Universiti Kebangsaan Malaysia, 2009)
This study empirically examines the stability and the main factors that have influenced the deposits in the Malaysian banking system. A structural model of the Malaysian money deposits applied to annual data for the 1983-2001 periods was designed. This structural model consists offve behavioural equations and three identities. A structural model functional form is used and estimated using the ordinary least squares in the log linear form. The behavioural equations are used to estimate the injluences of various factors on the conventional demand deposits, conventional time deposits, Islamic demand deposits, Islamic time deposits, and Islamic investment deposits. The implications of the study are that the increase in real gross domestic product, interest rate stability, and an increase in the profit-share for savings and investments are important for maintaining and enhancing the development of Malaysian money deposits. The results show that all the models (conventional and Islamic banks deposits) are stable; however Islamic demand deposits and Islamic time deposits are more stable than conventional demand deposits and conventional time deposits, because their Chow tests valzres are smaller than those of conventional deposits. The findings of this study suggests that as shariah compliant deposits are more stable than their conventional equivalents, then this makes a run on deposits less likely, reducing the potential amount of capital adequacy cover needed.